The Efficacy of SQ3R and Speed Reading Method in Improving Students’ Motivation to Learn and Reading Comprehension - Yuda, Lalu Setia; Mustadi, Ali (Journal of Languages and Language Teaching, 2025)
The application of the SQ3R (Survey, Question, Read, Recall/Recite, and Review) and Speed Reading methods is important to improve students' learning motivation and reading comprehension ability, which are essential basic skills in supporting successful learning in primary education. This study aims to determine: (1) the difference in the effect of SQ3R and Speed Reading method on learning motivation and reading comprehension ability. the difference in the effect of SQ3R method and Speed Reading method on learning motivation, and (2) the difference in the effect of SQ3R and Speed Reading method on reading comprehension ability. The research method was a nonequivalent control group pretest-posttest experiment. The research sample was purposive sampling technique of 96 fourth grade students. Data collection techniques and instruments are questionnaires and description test questions. Data analysis techniques using Manova test.  The results of this study indicate that: (1) there is a difference in the positive and significant effect of SQ3R method and Speed Reading method on learning motivation with a Sig value. 0.001 <0.05, and (2) there is a difference in the positive and significant effect of SQ3R method and Speed Reading method on reading comprehension ability with a Sig value. 0,001 < 0,05. The difference in the effect of SQ3R method and Speed Reading method on students' learning motivation and reading comprehension ability. The conclusion is that the SQ3R method is more effective for increasing learning motivation.